Ansätze zur Bewertung von Ausschuss - Marco Becker; Ulrich Krings (ZBW - Leibniz Information Centre for Economics, 2023)
Die kaufmännische Bewertung von Ausschuss stellt von je her in vielen Unternehmen ein Streitthema zwischen der Produktionsleitung, dem Qualitätsmanagement und der kaufmännischen Leitung dar. In der betrieblichen Praxis haben sich im Laufe der Jahre verschiedene Mechanismen zur kaufmännischen Bewertung von Ausschuss etabliert. In diesem Artikel sollen exemplarisch vier unterschiedliche Ansätze zur kaufmännischen Bewertung von Ausschuss systematisiert und hinsichtlich ihrer Vor- und Nachteile untersucht werden. – – The commercial evaluation of rejects has always been a subject of dispute between production management, quality management and commercial management in many companies. Over the years, various mechanisms for the commercial evaluation of scrap have become established in company practice. In this article, four different approaches to the commercial evaluation of scrap will be systematized and examined with regard to their advantages and disadvantages.The commercial evaluation of rejects has always been a subject of dispute between production management, quality management and commercial management in many companies. Over the years, various mechanisms for the commercial evaluation of scrap have become established in company practice. In this article, four different approaches to the commercial evaluation of scrap will be systematized and examined with regard to their advantages and disadvantages.
Keywords: L; 330; Qualität; Kosten; Ausschuss; Nacharbeit; Qualitätskosten; Total Costs of Quality